ANALISIS AIRFOIL (SAYAP PESAWAT) TERHADAP COEFESIEN LIFT (CL) DAN COEFESIEN DRAF (CD) DENGAN VARIASI KECEPATAN UDARA - Sukahar; Hafid, Achmad; Budi Santoso, Edy (PPM Sdirjianbang Akademi Militer, 2023)
Aerodynamic characteristics are a very important thing in the field of aerodynamic application science which is intended to obtain maximum performance from an object shape. This analysis was carried out to determine the effect of fluid flow velocity on symmetrical model aircraft wings. In this research, analysis of aerodynamic characteristics was carried out by testing an object in the form of a symmetrical model of an airplane wing that was supplied with air using a Wind Tunnel and Smoke Tunnel, so that the comparison and air flow produced could be seen. In connection with this, it is certain that we will not be separated from the topic of aerodynamics which is closely related to the characteristics of the object when flying in the air, which in the end will be able to draw conclusions regarding the aerodynamic characteristics of the object. In this final assignment, what will be discussed further are the aerodynamic parameters which in the world of aviation we usually know as the lift coefficient and also the drag coefficient. The method used is the simulation analysis method. The simulation was carried out by making a symmetrical aircraft wing model, then testing it using the Wind Tunnel and Smoke Tunnel tools. The purpose of this analysis is to determine the pressure characteristics of fluid flow on a symmetrical aircraft wing with a speed of 20 m/s and variations in angle of attack ranging from -20°, -10°, 0°, 10°, and 20° to the lift coefficient and drag coefficient and to determine the effect on each wing of a symmetrical model aircraft given speeds ranging from 12 m/s, 16 m/s, and 20 m/s which are fed by air in a wind tunnel using the drag coefficient and lift coefficient methods.